Особливості роботи з новітніми словниками української мови в закладі вищої освіти - Дворянкін, В. О.; Dvoriankin, V. O. (Наукові перспективи, 2025)
Визнано, що вміння користуватися словниками є вагомим як для здобувача вищої освіти, так і для фахівця-випускника, бо дотримання норм української літературної мови – важливий показник загальної культури особистості протягом усього її життя. Українську лексикографічну скарбницю постійно поповнюють нові праці. Це дає змогу викладачам-україністам використовувати словникову спадщину як цінний дидактичний матеріал у вишах, де здійснюють підготовку кадрів як філологічного, так і нефілологічного спрямування. Мета статті – схарактеризувати специфіку роботи з новітніми словниками української мови у вищій школі, що зумовило розроблення системи вправ на базі низки сучасних лексикографічних праць, визначення їх лінгводидактичного потенціалу як в аудиторії, так і в процесі самостійного опанування програмового матеріалу.

It is widely known that the ability to correctly use dictionaries is essential for both a higher education seeker and a university graduate, since adherence to the norms of literary Ukrainian is an important lifelong factor of a personality’s general culture. The Ukrainian lexicographical treasury is permanently being refilled by new works. This makes it possible for teachers of Ukrainian to use the lexicographical heritage as a valuable didactical material in universities training personnel of both philological and non-philological fields of knowledge. The goal of the article is to characterize the specificity of working with the latest dictionaries of the Ukrainian language in higher school, which predetermined development of a system of exercises based on a number of modern lexicographical works, identifying their linguodidactical potential both in the classroom and in the process of independent mastering of the teaching prescribed stuff.
Peculiarities of working with the latest dictionaries of the ukrainian language in a higher education institution
Keywords: новітні словники української мови; робота зі словниками; дидактичний матеріал; лінгводидактичний потенціал; система вправ; лексикографічна компетенція; latest dictionaries of the Ukrainian language; work with dictionaries; didactical material; linguodidactical potential; system of exercises; lexicographical competence